Rice Bowl Tuna Balado: Inovasi Usaha Rumahan untuk Kemandirian Ekonomi Kelurahan Kampung 4. - Nurul Hidayat; Cikha Aryan; Elvi Mayli; Nur Alisah; Rahmat Hidayat; Reni Handayani; Yoel Anis (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
Kampung 4 Village has great potential in developing home-based culinary businesses as a strategy to increase family economic independence. One promising business opportunity is Tuna Balado Rice Bowl, a practical food product that combines tuna as the main ingredient with the distinctive flavor of balado. This product has broad market prospects because it is easy to produce, has high nutritional value, and is in line with the trend of fast food that is in demand by various groups. In addition, this business can be run with relatively affordable capital and has broad marketing potential through digital strategies such as social media and delivery services. Seeing these opportunities, the Tuna Balado Rice Bowl business can be an alternative home-based business that is competitive, able to increase family income, and contribute to strengthening the local economy in a sustainable manner.